Association between bullying and risky eating behaviors among adolescent population of Metropolitan Lima and Callao - Padilla Lay, Martin Clímaco (2025)
Objectives: Exploration and eventual establishment of an association between school bullying and risky eating behaviors (REB) in adolescents from Lima Metropolitan Area and Callao. Materials and methods: Observational, cross-sectional, and analytical study, based on data from the Epidemiological Study conducted by the National Institute of Mental Health in 2012. The sample included 1,490 adolescents aged 12 to 17. Scores from the bullying scale and the REB Questionnaire, along with sociodemographic variables, were used. Bivariate analyses were conducted to evaluate the association between bullying, REB, and sociodemographic variables. A binary logistic regression model was proposed to explain REB, supplemented by Odds Ratios (OR) and prevalence data. Results: The observed annual prevalence rates were 43.8% for bullying and 23.5% for REB. Bullying showed a significant association with poverty level (p<0.01), and REB with sex and age (p<0.05 for both). Bullying and REB also showed a significant association (p<0.001). The explanatory model for REB showed a good fit (p<0.001), with significant predictors: bullying (p<0.001), sex (p<0.05), and age (p<0.05). Conclusions: A significant association between bullying and REB was confirmed. The proposed explanatory model reveals that being female, aged 15 to 17, and being a victim of bullying are risk factors contributing to the presence of REB in adolescents. Preventive strategies for REB should include addressing bullying in the school environment, with special attention to vulnerable groups.